Implementasi Kebijakan Pendaftaran Tanah Sistematis Lengkap (PTSL) Badan Pertanahan Nasional (BPN) Kabupaten Tegal pada Masa Pandemi Covid-19 Tahun 2020-2021 - Suharto, Suharto; Firdian, Zidane Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2023)
This study aims to determine the implementation of the Complete Systematic Land Registration (PTSL) program at the Tegal Regency Land Agency. The type of research used is qualitative research. The collection of data used is observation, literature study and interviews. The data analysis technique used is descriptive analysis, namely by collecting data related to data collection techniques carried out and obtained by the author. Then the data is processed with the aim of getting a clear picture related to the research focus and the writer performs a descriptive analysis in writing the results of his study.The results of this study indicate that the implementation of policies carried out by the Tegal Regency Land Agency in the PTSL program has been carried out well, but with a note that there must be an increase in debriefing, effective coordination and communication to the field committee, as well as more active outreach to the community, especially for those who living in another area or migrating. In terms of the contents of the policy providing a beneficial impact on the community, from the support of the community in this program to being involved in the process of implementing the PTSL program, the distribution of potential is carried out by giving responsibility and authority to the Village Office and the community involved in the PTSL program. As for the inhibiting factors, namely the existence of some people who lack the socialized PTSL program, incomplete files owned by the community, issues of inheritance rights that have not been resolved, boundary disputes, difficult terrain at several measurement points and field coordination which often results in misunderstandings in communication.Â